2009
DOI: 10.1080/00665983.2009.11078221
|View full text |Cite
|
Sign up to set email alerts
|

Dating Celtic Art: a Major Radiocarbon Dating Programme of Iron Age and Early Roman Metalwork in Britain

Abstract: This paper presents the first substantial set of radiocarbon determinations for the later Iron Age decorated metalwork known as Celtic art in Britain. Hitherto this material has been dated relatively on the basis of changes in decoration and form, which were then linked to materials with some absolute date. The latter process has tended to give relatively late dates, as most of the material with a firm date stems from the last century BC or after. This has meant that British Celtic art appears to be rather lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 35 publications
2
42
0
1
Order By: Relevance
“…BC (68 per cent probability). These results are similar to those obtained by Garrow et al (2009), who discuss the earlier dating indicated for some of the burials. A comparison of modelled probability density functions for the chariot burials is given in Figure 9.…”
Section: Questioning the Timing And Utility Of Existing Chrono-typolosupporting
confidence: 82%
See 4 more Smart Citations
“…BC (68 per cent probability). These results are similar to those obtained by Garrow et al (2009), who discuss the earlier dating indicated for some of the burials. A comparison of modelled probability density functions for the chariot burials is given in Figure 9.…”
Section: Questioning the Timing And Utility Of Existing Chrono-typolosupporting
confidence: 82%
“…BC (Nowakowski and Quinnell 2011, 141-5, 163-85), both earlier than was thought before the advent of radiocarbon dating. Our ongoing work in the Danebury area suggests that Bury Hill hillfort was occupied in the second rather than the first century BC, confirming the earlier dating for decorated horse and chariot equipment deposited in the interior indicated by the Celtic Art project (Garrow et al 2009). Lastly, at Conderton Camp the modelling provided an earlier than expected date for the building of the hillfort and strongly suggests that in places the relative order of structures suggested from the pottery may be incorrect (Thomas 2005, 237-45).…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations